Queer spawn on school - Rachel Epstein; Becky Idems; Adinne Schwartz (Linköping University Electronic Press, 2013)
This article is about the school experiences of young people with LGBTQ parents. Based on 31 interviews with youth, ages 10-18, the article attempts to summarize what these young people had to say about the challenges they encounter in school, and the strategies they adopt in the face of them.